(untitled) (Research, Society and Development, 2020)
Three-dimensional (3D) contouring has become very important in industry and in many other production systems. The optical techniques provide many attractive properties for such measurement due to their precision, reliability, accuracy and ability to measure small and fragile objects. In this work we report the study, the development and the performance of a low-cost optical device based on interferogram projection in order to measure the sub-millimetric relief of polymeric plates containing biomimetic textures used in the automotive industry. The interferogram was generated by a Twyman-Green interferometer illuminated by a 532-nm green laser. The measurement was performed by means of phase-shifting and phase-unwrapping procedures and the results were benchmarked with the ones obtained by a commercial device.